2011
DOI: 10.1021/jo201563b
|View full text |Cite
|
Sign up to set email alerts
|

Nonconcerted Cycloaddition of 2H-Azirines to Acylketenes: A Route to N-Bridgehead Heterocycles

Abstract: Reactions of acylketenes, generated from diazo diketones, with 2-unsubstituted and 2-monosubstituted 3-aryl-2H-azirines lead to 1:1 or 2:1 adducts, which are derivatives of 5-oxa-1-azabicyclo[4.1.0]hept-3-ene or 5,7-dioxa-1-azabicyclo[4.4.1]undeca-3,8-diene. According to DFT B3LYP/6-31G(d) computations, the formation of (4+2)-monoadducts proceeds via a stepwise non-pericyclic mechanism. Reaction with methanol transforms quantitatively both 1:1 and 2:1 adducts into 1,4-oxazepine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The formation of compounds 3 proceeds in the same way as for similar compounds obtained by reaction of azirines with acylketenes from diazo compounds (Scheme 2) [22]. According to the calculation at the DFT B3LYP/6-31G(d) level with PCM solvation model for benzene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of compounds 3 proceeds in the same way as for similar compounds obtained by reaction of azirines with acylketenes from diazo compounds (Scheme 2) [22]. According to the calculation at the DFT B3LYP/6-31G(d) level with PCM solvation model for benzene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 H -Azirines can react with ketenes both with cleavage and preservation of the three-membered ring [2226]. It was found that acylketenes, which are generated in situ from diazo ketones, undergo cycloaddition with 3-mono- and 2,3-disubstituted-2 H -azirines to afford 2:1 or 1:1 adducts: 5,7-dioxa-1-azabicyclo[4.4.1]undeca-3,8-diene or 5-oxa-1-azabicyclo[4.1.0]hept-3-ene derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…91 The quenching of ketenes can also be performed by 2H-azirines whereas the resulting zwitterion proceeds to the formation of (4 þ 2) monoadducts through a stepwise nonpericyclic mechanism. 92 In the context of organic synthesis, the entrapment of ketenes derived from the Wolff rearrangement with amines has been explored in the preparation of amides in good yields (68-92%) using microwaves to promote the ketene formation, 33 as well as amide formation of a ketose derivative employing silver salts as rearrangement promoter, 93 or in the modification of ferrocene derivatives. 94 A photolabile end functionalized monomethyl poly(ethylene glycol) containing a terminal a-diazo ketone moiety was used to monofunctionalize lysozyme and ribonuclease.…”
Section: Reactions Of Ketenes Derived From the Wolff Rearrangement Wimentioning
confidence: 99%